2019
DOI: 10.3390/nu11112692
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hydration Status and Body Composition in Healthy Adolescents from Spain

Abstract: At present, obesity and overweight are major public health concerns. Their classical determinants do not sufficiently explain the current situation and it is urgent to investigate other possible causes. In recent years, it has been suggested that water intake could have important implications for weight management. Thus, the aim of this study was to examine the effect of hydration status on body weight and composition in healthy adolescents from Spain. The study involved 372 subjects, aged 12–18 years. Water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…A cross-sectional study conducted among young adults in China revealed a moderate correlation between water intake and body composition (such as the TBW/BW), in both males and females [ 24 ]. Similarly, in children, the water intake normalized by body weight is positively correlated with body water content, for both boys and girls [ 25 ]. Nevertheless, studies have demonstrated that approximately 50–65% of children and adults do not achieve the European Food Safety Association (EFSA) recommendation for total drinking fluids [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study conducted among young adults in China revealed a moderate correlation between water intake and body composition (such as the TBW/BW), in both males and females [ 24 ]. Similarly, in children, the water intake normalized by body weight is positively correlated with body water content, for both boys and girls [ 25 ]. Nevertheless, studies have demonstrated that approximately 50–65% of children and adults do not achieve the European Food Safety Association (EFSA) recommendation for total drinking fluids [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…PHA could re ect the water distribution between the intracellular and extracellular water compartments (42). Previous studies had shown an inverse relationship between BMI and water balance (49), due to greater hydration and uids in the extracellular compartments, obese people had a higher ECW/ICW ratio than non-obese people (42,50), and in healthy people, ECW/ICW ratio was an important determinant of the PHA(26). However, in our study, we didn't nd a signi cant change in the value of ECW/ICW with BMI increased.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obesity have a multifactorial etiology involving genetic predisposition and multiple environmental factors, which include energy intake, activity level, composition of gut microflora, sedentary behavior, endocrine diseases, hydration status and/or socioeconomic position, among others [1,[13][14][15]. The first and key step to develop prevention and repair strategies for intervention before damage becomes irreversible is to develop programs to prevent childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obesity are the result of an imbalance between energy intake and expenditure that leads to positive energy balance being associated with lifestyle (activity level) and dietary intake [12]. However, currently it is well known that obesity is influenced by other factors such as genetic background, composition of gut microflora, sedentary behavior, endocrine diseases, hydration status and/or socioeconomic position, among others [1,[13][14][15]. Currently, there is great evidence available in the literature suggesting the association between socioeconomic status and the development of childhood obesity.…”
Section: Introductionmentioning
confidence: 99%